Avaliação do nível de satisfação, capacidade, eficiência e performance mastigatórias em pacientes reabilitados com próteses fixas totais inferiores sobre implantes, sob carga imediata - Carvalho, Luiz Eduardo Pinto de (2002)
Problems associated with retention and stability of conventional removable total prostheses damage the function, aesthetics, psychological health and social relations of their wearers. Rehabilitations with prostheses on implants provide greater safety and comfort for these patients. It is important to understand the patients’ wishes and needs, so as to attain their expectations and solve their problems. In order to evaluate the quality of rehabilitating therapies offered to patients, controls can be carried out while treatments are being performed and after their completion. Aiming at discussing and providing simple and reproducible methodologies to verify the Masticatory Capacity (MC), Level of Satisfaction (LS), Masticatory Efficiency (ME) and Masticatory Performance (MP), 16 totally edentulous patients rehabilitated with lower fixed prostheses on implants, under immediate load, were evaluated in three distinct moments. MC and LS, provided by the patients themselves through their answers to questionnaires, and ME, obtained by the mastication of almonds, were significantly greater at the moments of 30 days and 4 months following treatment, in relation to the preoperative moment, when they still carried upper and lower conventional removable total prostheses, though not significant among them. The MP, obtained through mastication tests with Optosil (Heraeus Kulzer), showed significant differences among moments preoperative, 30 days and 4 months following treatment performed. It was observed that this treatment propitiated better life quality and, that the dentist’s sensibility in perceiving the longings of his patients favors treatments that meet their real needs